Kualitas Pemahaman Pelayanan dan Kepuasan Wajib Pajak setelah Penggunaan Coretax System - Elvina, Santi; Ari Pertiwi, Dwi (Universitas Muhammadiyah Ponorogo, 2025)
Digital transformation in tax administration encourages the implementation of more integrated information technology through the use of the Coretax System. This system is designed to improve efficiency, accuracy, and transparency in the tax process, as well as facilitate taxpayers in fulfilling their tax reporting and payment obligations. This study aims to determine the quality of service understanding and taxpayer satisfaction levels after the implementation of the Coretax System. The method used in this study is a qualitative descriptive method with data collection techniques such as interviews, observations, and documentation conducted at the Tax Service Office (KPP). The results show that the implementation of the Coretax System can improve taxpayer understanding of tax procedures through a user-friendly interface, clear system guidance, automatic validation, and tax obligation notifications. Furthermore, taxpayer satisfaction levels also increase due to ease of access, time efficiency, process transparency, and greater data security. However, several obstacles remain in its implementation, such as differences in digital literacy levels and technical constraints in the initial stages of implementation. Therefore, increased socialization, training, and continuous system development are needed so that the Coretax System can run more optimally and provide maximum benefits for taxpayers and the state. Keywords: Coretax System, tax services, taxpayer satisfaction.